Environmental accounting and its importance in sustainable environmental development: 'Case Study of the Sirte Steam Station (Journal of Academic Research, 2020)
The aim of this research is to try to identify the importance of environmental accounting in achieving sustainable environmental development in Libyan industrial enterprises. As environmental accounting is an effective system governing the environmental performance in the institution and considering that environmental accounting is concerned with the preparation of accounts based on environmental dimension, this in turn would be reflected on the conservation and sustainability of natural resources. The study attempts to identify the role and importance of environmental accounting in reducing environmental pollution. The research community consisted of all power plants in Libya, and the case study of the steam power plant in Sirte was selected as a representative sample of the research community. The questionnaire methodology was used as a tool to achieve the objectives of the research. Then the research utilized the statistical descriptive method using SPSS to analyze the results.  The research has reached a number of results, the most important of which is that there are no statistically significant differences in the attitudes of the research sample on environmental accounting as well as sustainable environmental development in the steam station Sirte attributed to educational level, current job, years of experience, as it was found that there is a significant relationship statistics between environmental accounting and sustainable environmental development in Sirte steam station.
Keywords: Environmental Accounting; Sustainable Environmental Development; Sirte Steam Station